Overvoltage and Oscillation Analysis for a Full-Bridge Isolated DC-DC Converter - Avdeev, Boris A.; Vyngra, Aleksei V.; Zhilenkov, Anton A.; Chernyi, Sergei G.; Degtyarev, Andrey; Kustov, Aleksandr; Zinchenko, Anton (Universitas Muhammadiyah Yogyakarta, 2024)
The paper deals with determining and eliminating overvoltage’s and ripples from the output of a high-frequency inverter bridge in a full-bridge DC converter. These oscillations can cause overvoltage on the elements of the power converter, which in turn can lead to false triggering of semiconductor keys or their failure. Schematic diagrams of the bridge are given; the principle of its operation is described. A simplified equivalent circuit replaces the classic bridge. A qualitative analysis of transient processes in the resulting scheme is made. The voltage at the output of the bridge is found using the operator method. The findings have been compared with the simulation model executed in MATLAB/Simulink. The presented method is less labor-intensive than simulation modeling and allows for faster and easier verification of the permissible overvoltage level and oscillation frequency, which is especially important in devices containing a large number of nonlinear elements. It is shown how the parameters of the bridge affect the performance of the transient, in particular the overshoot and oscillation frequency. The attained dependencies are shown in graphical form. The ways of improving the quality of the transition process are given. The findings have been verified on an experimental setup. The obtained theoretical results are consistent with the results of the experiment with the data of other researchers.